Obstructed infracardiac total anomalous pulmonary venous connection: The challenge of palliative stenting for the stenotic vertical vein - Mansour Al‐Mutairi; Adnan Aselan; Mustafa Al‐Muhaya; Hany Abo‐Haded (Wiley, 2020)
ABSTRACT Introduction Obstructed total anomalous pulmonary venous connection (TAPVC) is one of the commonest seen emergencies in pediatric cardiology centers. Case presentation Our case was diagnosed to have this anomaly, showing early respiratory distress resulting from severe pulmonary congestion. Palliative stenting of the obstruction was done, which helped in stabilizing the debilitated hemodynamics of the baby before surgery, thus a good surgical outcome and prognosis are expected. Conclusion This intervention may be listed as a vital measurement in the preoperative cardiac stabilization plan for infants with obstructed TAPVC.